Contextual Factors Contributing to Adaptive Coping in Adolescents Under Academic Stress - Rahman, Farhana; Mokoena, Thandiwe (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the contextual, personal, and sociocultural factors that contribute to adaptive coping among adolescents experiencing academic stress, with a focus on understanding how environmental and individual elements interact to promote resilience.Methods and Materials: A qualitative research design was employed using an exploratory and descriptive approach. Seventeen adolescents (aged 14–18) from three secondary schools in Gauteng Province, South Africa, were selected through purposive sampling. Semi-structured interviews were conducted to capture participants’ lived experiences of academic stress and coping strategies. Data collection continued until theoretical saturation was reached. Interviews were transcribed verbatim and analyzed thematically using NVivo 14 software. Trustworthiness was ensured through member checking, peer debriefing, and maintaining an audit trail in accordance with Lincoln and Guba’s criteria of credibility, dependability, and confirmability.Findings: Analysis revealed four overarching themes: (1) Supportive Social Environment, encompassing family, peer, and teacher support as key buffers against stress; (2) Personal Coping Strategies, highlighting cognitive reframing, emotional regulation, and proactive help-seeking as adaptive mechanisms; (3) Academic and Institutional Context, identifying positive school climates and counseling services as facilitators of resilience; and (4) Cultural and Socioeconomic Influences, showing how family expectations, community values, and financial pressures both intensified and motivated coping responses. The findings indicated that adaptive coping is a multidimensional process rooted in the interaction between psychological flexibility, relational support, and cultural meaning-making.Conclusion: Adolescents’ ability to cope adaptively with academic stress depends on the convergence of personal resilience, supportive relationships, and culturally grounded values. Enhancing school-based and community-level support structures can strengthen adolescents’ capacity to transform academic pressure into personal growth and adaptive functioning.